Critical reading of clinical studies. Practical bases for the resident physician in medical specialties: Lectura crítica de estudios clínicos. Bases prácticas para el médico residente de especialidades clínicas - Pichardo-Rodríguez, Rafael (2021)
Critical reading from the point of view of evidence-based medicine is a structured reading that allows us to evaluate the validity and relevance of the results and the applicability of a clinical study in our patient. However, the level of critical reading in resident physicians is low, as various studies have described. In a study of oncology resident physicians, a poor level of critical reading of clinical research articles was found. And in the same way, deficient levels were found in cardiology and family medicine residents. In our country, this situation is unknown and it is most likely deficient. Reason why we prepared a small review to be able to share practical bases that help the resident of specialties apply in a simpler way the critical reading of clinical studies.